CD44 EXPRESSION LEVELS AS A BIOMARKER FOR THE EARLY DETECTION OF VARIOUS CANCERS IN BIOLOGICAL SAMPLES: A CASE- CONTROL STUDY - Bsharat, Samah (An-Najah National University, 2025)
BACKGROUND: Cancer stem cells (CSCs) contribute to tumor progression, metastasis, and therapy resistance, with CD44 playing a key role in CSC function. As a transmembrane glycoprotein, CD44 interacts with ligands like hyaluronic acid, regulating adhesion, migration, and signaling pathways (Ras-MAPK/ERK). Its alternative splicing and modifications enhance functional diversity, promoting chemoresistance and metastasis. Elevated CD44 expression in aggressive cancers, including breast and colorectal malignancies, highlights its potential as a diagnostic biomarker and therapeutic target. Given its role in tumor progression, this study aims to evaluate soluble CD44 as a biomarker for the early detection and differentiation of breast and colorectal cancer. By analyzing its expression levels in blood and urine across different cancer stages and types, this research seeks to establish CD44’s diagnostic value and potential contribution to precision medicine in oncology. METHODS: This case-control study (2023–2024) examined CD44 expression as a biomarker for breast cancer (BC) and colorectal cancer (CRC) at three hospitals in Nablus, including 40 BC patients, 23 CRC patients, and 70 healthy controls. Blood and urine samples were analyzed for CD44 gene and soluble forms, with exosomal RNA quantified via real-time PCR (normalized to GAPDH) and soluble CD44 levels measured using ELISA. Statistical analyses (two-way ANOVA, t-tests, p ≤ 0.05) confirmed significant differences, ensuring accuracy through standardized protocols. RESULTS: The research indicates a very strong statistically significant elevation in CD44 expression in breast cancer patients when compared to healthy controls (p < 0.0001) in both fold change (gene expression) and soluble CD44 (sCD44) serum and urine concentrations. Similarly, a moderate statistically significant elevation (p < 0.01) in CD44 gene expression form and soluble form for CRC patients compared to healthy controls. Furthermore, there is a strong statistically significant difference in CD44 expression between patients with breast cancer and those with colorectal cancer (p < 0.001). CONCLUSIONS: The study identified significantly elevated sCD44 levels in serum and urine of breast and colorectal cancer patients, supporting its potential as a cancer biomarker. In contrast, αFP showed minimal diagnostic value, with negligible serum changes and absence in urine, reinforcing its association with liver-related cancers.
مستويات تعبير CD44 كعلامة حيوية للكشف المبكر عن أنواع السرطان المختلفة في العينات البيولوجية: دراسة الحالات والشواهد